2005
DOI: 10.1007/s11064-005-6865-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Evidence for Agmatine Modulation of 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine (MPTP) Neurotoxicity

Abstract: Agmatine treatment is known to exert neuroprotective effects in several models of neurotoxic and ischemic brain and spinal cord injuries. Here we sought to find out whether agmatine treatment would also prove to be neuroprotective in the mouse 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) model of Parkinson's disease. Concomitant daily treatment (intraperitoneal injections) with agmatine (100 mg/kg for 5 days) and MPTP (40 mg/kg for 2 days) exacerbated MPTP-related toxicity as evidenced by a larger reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Once released, agmatine acts on different transmembrane receptors, including the imidazoline receptor (Aricioglu et al, 2003;Wu et al, 2005), the ␣ 2 -adrenergic receptor (␣ 2 -AR) and the glutamatergic NMDA receptor (Halaris and Plietz, 2007;Yang and Reis, 1999). Agmatine has both anti-neurotoxic (Gilad et al, 2005;Zhu et al, 2006) and antidepressant actions (Halaris and Piletz, 2003) thereby helping to relieve psychological stress (Halaris and Plietz, 2007).…”
Section: Agmatinementioning
confidence: 99%
“…Once released, agmatine acts on different transmembrane receptors, including the imidazoline receptor (Aricioglu et al, 2003;Wu et al, 2005), the ␣ 2 -adrenergic receptor (␣ 2 -AR) and the glutamatergic NMDA receptor (Halaris and Plietz, 2007;Yang and Reis, 1999). Agmatine has both anti-neurotoxic (Gilad et al, 2005;Zhu et al, 2006) and antidepressant actions (Halaris and Piletz, 2003) thereby helping to relieve psychological stress (Halaris and Plietz, 2007).…”
Section: Agmatinementioning
confidence: 99%
“…A solution to their origins comes from the idea that PAs are probably taken up from external sources by glial cells. 114, 126, 194 It has been hypothesized that PAs are taken up by glia from the blood circulation, cerebral spinal fluid (CSF) or from macrophages penetrating the blood-brain barrier. One of the possible pathway is the organic cation transporter (OCT) system which is expressed in glia.…”
Section: Interaction Of Polyamines With Receptors and Ion Channelsmentioning
confidence: 99%
“…9, 78, 80, 239244 It was suggested that PAs could be taken up from external sources by glial cells via hypothetical transporters which would bring PAs into the cells 114, 126, 194,195 by transporters localized at the endfeet that are attached to blood vessels and brain ventricles. According to this view, the blood circulation and CSF would be the major sources of PA uptake.…”
Section: Interaction Of Polyamines With Receptors and Ion Channelsmentioning
confidence: 99%
“…5A, a significant reduction on the VCM frequency was observed in mice administered with 7-NI at doses of 1 and 10 mg/kg [F (4,28) =9.41; P<0.0001]. Fig.…”
Section: Role Of Nos Inhibition In the Agmatine Orofacial Antidyskinementioning
confidence: 80%
“…The ability of agmatine to act as reactive oxygen species (ROS) scavenger, protecting against oxidative stress-induced mitochondrial dysfunction and apoptosis [25,26] is also remarkable. Finally, agmatine emerges as a potential agent to manage diverse CNS disorders (for review, see [27]), including PD [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%